Increase in Profit Based on Internal Capital and Business Volume in Cooperatives in Indonesia - Azhari, Azhari (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The cooperatives in Indonesia have hundreds of thousands, but not all are active due to several factors, including member participation, revenue, assets, and external capital. The purpose of this study is to provide the dominant factors that affect the operating profit of cooperatives. This research is quantitative causality, with data from 2001-2021 and multiple regression as an analysis tool. The data source was obtained from the Ministry of Cooperatives and SMEs. The analysis results show that the variables of own capital and sales volume simultaneously affect the remaining operating results, while partially owned capital does not affect cooperative profits. This research can evaluate increasing cooperative profits through policies that can be applied to cooperatives.